Officiating wrestling (Human Kinetics, 2006)
"Supported by more than 100 photos and illustrations of proper positioning and signaling, this book includes real-life cases to demonstrate correct rulings and to point out common officiating errors and how to avoid them. Officiating Wrestling is not a rules book; it's a practical resource for implementing correct mechanics as developed and approved by the NFHS."--BOOK JACKET.